Implementasi Pendidikan Karakter Sopan Santun Siswa Melalui Media Cantik di SD Negeri 11 Mataram - Hidayani, Baiq Nurul (Jurnal Paedagogy, 2021)
This study aims to describe the implementation of the character education of students’ courtesy through beautiful media at SD Negeri 11 Mataram. This research method using descriptive method. Data collection techniques in this study using observation and documentation. The data analysis technique used thematic analysis. The results of this study indicate that the use of beautiful media in improving the character of courtesy of students at SD Negeri 11 Mataram shows the results and can provide concrete experiences for students in being polite in everyday life, especially at school.